“You Look Fat in Red”: Fat Talk in the Workplace - Desy Catur Karinatasa; Emy Sudarwati (OKARA: Jurnal Bahasa dan Sastra, 2021)
In the Indonesian context, commenting on one's less adequate body size is considered normal. However, the effect it has on the person who is subjected to it is quite surprising. The fat talk phenomenon in the workplace is one example of fat talk case that remains under-researched. This research reflects the phenomenon of fat talk in the workplace viewed from a sociolinguistics viewpoint. In analyzing and gathering the evidence, this research uses a descriptive qualitative approach and citizen sociolinguistics. The data were obtained from the discovery made by citizen sociolinguists in the workplace. Based on Bulik's 12 types of fat talk, the results showed that the most frequent types are personalized and generic (24%), followed by compliment fishing and bullying (21%). The least used types of fat talk are comparative, joking, and fat-is-ugly. The results also showed that the fat talk's linguistic features were found to be linked to body parts, clothing, food, body health, appearance, weight, and context of appearance and height. Eventually, fat talk is a new language variation that has fulfilled a specific language purpose in the workplace.